PEMBERDAYAAN KADER DALAM PENATALAKSANAAN IBU HAMIL KEK BERBASIS TEKNOLOGI INFORMASI DALAM UPAYA PENINGKATAN STATUS GIZI IBU HAMIL DI DESA OLOBOJU WILAYAH KERJA PUSKESMAS BIROMARU KABUPATEN SIGI - Irnawati, Irnawati; Fadlhi, Wendy Muhammad; Asmi, Nur; Dyastuti, Nur Eka; Matoka, Natasya S.; Astrid, Ratri; Mukaromah, Lailatul; Faradillah, Faradillah; Kristiani, Kristiani; Alamsah, Asniati; Misra, Misra; Butudoka, Eka Pratiwi K.; Zaitun, Zaitun; Ramadani, Gina (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2025)
Chronic energy deficiency in pregnant women is a condition where pregnant women suffer from nutritional deficiencies for a long time (chronic) which results in health problems for pregnant women and their unborn children. The aim of this local food diversity training is to teach cadres how to process Moringa leaves into various interesting and nutritious foods, so that cadres and pregnant women don't get bored with just one processing method. Community service activities with the theme Empowerment of cadres in the management of pregnant women using information technology using education and training methods targeting cadres and pregnant women in Oloboju village. The level of knowledge before counseling was carried out for pregnant women in the good category was 11.1%, the sufficient category reached 22.2%, and the poor category was 66.7%. After counseling, the good category increased to 100%. Thus, there was an increase before and after counseling for pregnant women and training for cadres